Investigation of growth dynamics of carbon nanotubes - Kharlamova, Marianna V. (Beilstein Journal of Nanotechnology, 2017)
The synthesis of single-walled carbon nanotubes (SWCNTs) with defined properties is required for both fundamental investigations and practical applications. The revealing and thorough understanding of the growth mechanism of SWCNTs is the key to the synthesis of nanotubes with required properties. This paper reviews the current status of the research on the investigation of growth dynamics of carbon nanotubes. The review starts with the consideration of the peculiarities of the growth mechanism of carbon nanotubes. The physical and chemical states of the catalyst during the nanotube growth are discussed. The chirality selective growth of nanotubes is described. The main part of the review is dedicated to the analysis and systematization of the reported results on the investigation of growth dynamics of nanotubes. The studies on the revealing of the dependence of the growth rate of nanotubes on the synthesis parameters are reviewed. The correlation between the lifetime of catalyst and growth rate of nanotubes is discussed. The reports on the calculation of the activation energy of the nanotube growth are summarized. Finally, the growth properties of inner tubes inside SWCNTs are considered.
Keywords: activation energy; carbon nanotube; growth dynamics; growth rate; synthesis